Beware of neonatal appendicitis - Khan Rizwan; Menon Prema; Rao K. L. N. (Wolters Kluwer Medknow Publications, 2010)
We report a neonate with acute appendicitis who was mistakenly diagnosed and treated initially as neonatal necrotizing enterocolitis. The diagnostic dilemma of this rare and life-threatening condition in premature babies and newborns is underlined. Awareness of this rare condition and possible differential diagnosis in this age group is also discussed.